Managing the learning process in rural development the case of the DENR's upland development program - Borlagdan, Salve B. (1993)
Since its implementation in the early '80s, the Upland Development Program (UDP) of the DENR has attempted to operationalize the "learning process approach' in rural development planning. Directed to the development of the social forestry program as the principal learning agenda, this approach posits that the key to the program's success is to learn by doing. Thus, the program embarked on two major objectives: (1) to operationalize the participatory approach towards organizing uplanders for the protection and management of upland resources while simultaneously addressing poverty; and (2) to develop the necessary institutional capacities for effective implementation of such approach. Although the UDP can boast of its many accomplishments, there is still much to be done to effectively implement the program in a participatory manner. Moreover, it has to respond to the urgent call of devolution brought about by the new Local Government Code.
Keywords: Rural development; Upland Development Program